ANALISIS DAMPAK REVITALISASI ALUN-ALUN KOTA MALANGDALAM MENINGKATKAN DAYA TARIK WISATA - Achmad Faruq Mafalsa; Djamhur Hamid; . Sunarti (Jurnal Administrasi Bisnis, 2016)
Malang City Square was one of the tourist destination in the Malang, reopen in 2015 after undergoing the revitalization. The project of Malang City square expected to have good impact in several aspects. This research used the descriptive qualitative and data sources obtained from interview. This research purpose to knowing impacts revitalization of Malang City Square. The impact of revitalization Malang City Square  the religious namely the establishment of a special place prayer,On the security operating police park, on educational aspect there are several facilities educate the library, on the social the increasing number of a community that got together in a square increase the dynamics and community social life, on the economic impact on income sector parking the crowded as the amount of the visitor, on the culture that is the development of culture more modern as style of dress and the effects on the physical aspects that is the establishment of the several new buildings and rejuvenation number of buildings. The effects on tourism attractiveness is the increase in tourist attractiveness because there were facilities and new innovations after revitalization makes visitors interested to come to the square. Keyword : The Malang City Square,  impact of revitalization, and the tourist attraction. ABSTRAK Alun-Alun Kota Malang merupakan salah satu tempat wisata di Kota Malang yang dibuka kembali pada tahun 2015 setelah menjalani masa revitalisasi. Proses revitalisasi Alun-Alun Kota Malang diharapkan berdampak baik pada beberapa aspek yang ada. Penelitian ini menggunakan metode deskriptif kualitatif dan pengumpulan data melalui wawancara. Tujuan penelitian ini adalah untuk mengetahui dampak revitalisasi Alun-Alun Kota Malang. Dampak dari revitalisasi Alun-Alun Kota Malang yaitu pada aspek religi tersedianya tempat khusus untuk menampung jamaah masjid jami, pada aspek keamanan tersedianya polisi taman, pada aspek pendidikan tersedianya perpustakaan, pada aspek sosial meningkatnya dinamika sosial, pada aspek ekonomi meningkatnya pendapatan pada sektor parkir, pada aspek budaya yaitu terjadinya pergeseran budaya, pada aspek fisik yaitu penambahan beberapa fasilitas seperti playground di alun-alun. Meningkatnya daya tarik wisata Alun-Alun Kota Malang terjadi dikarenakan revitalisasi pada beberapa aspek tersebut. Kata Kunci: Alun-Alun Kota Malang, Dampak Revitalisasi, Daya Tarik Wisata